1979
DOI: 10.1243/pime_proc_1979_193_019_02
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Thickness of Grease and Oil Films in Rolling Bearings

Abstract: A method for measuring the thickness of grease films between the rollers and rings of rolling bearings is described. Measurements in two designs of bearing show that a grease can initially form thicker films than can its base oil but that, without frequent relubrication, the grease films become slightly the thinner with time. The thinning of grease films, which is attributed to partial starvation, is accompanied by a reduction in viscous friction. Except in critical applications, where the thickest films are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 6 publications
2
40
0
Order By: Relevance
“…Wilson [1] observed this phenomenon in a rolling bearing in 1979. Zhu and Neng [2] then measured the large decrease of film thickness in a starved grease lubricated point contact.…”
Section: Introductionmentioning
confidence: 89%
“…Wilson [1] observed this phenomenon in a rolling bearing in 1979. Zhu and Neng [2] then measured the large decrease of film thickness in a starved grease lubricated point contact.…”
Section: Introductionmentioning
confidence: 89%
“…Other experimental studies with lubricating greases may be found in [6][7][8][9][10]. All these research works suggest the same grease film formation mechanism: initially grease builds-up a higher film thickness than its base oil, but it decreases with time and reaches a starved condition.…”
Section: Introductionmentioning
confidence: 96%
“…By definition according to Wilson [23], the onset of starvation occurs at the above described characteristic rolling speed. This study focuses on measurements under starved grease lubrication and the onset of starvation will be pointed out by following the definition by Wilson [23].…”
Section: Introductionmentioning
confidence: 99%